HES6 promotes prostate cancer aggressiveness independently of Notch signalling. Issue 7 (12th April 2015) - Carvalho, Filipe L. F.; Marchionni, Luigi; Gupta, Anuj; Kummangal, Basheer A.; Schaeffer, Edward M.; Ross, Ashley E.; Berman, David M.
Abstract Notch signalling is implicated in the pathogenesis of a variety of cancers, but its role in prostate cancer is poorly understood. However, selected Notch pathway members are overrepresented in high‐grade prostate cancers. We comprehensively profiled Notch pathway components in prostate cells and found prostate cancer‐specific up‐regulation of NOTCH3 and HES6. Their expression was particularly high in androgen responsive lines. Up‐ and down‐regulating Notch in these cells modulated expression of canonical Notch targets, HES1 and HEY1, which could also be induced by androgen. Surprisingly, androgen treatment also suppressed Notch receptor expression, suggesting that androgens can activate Notch target genes in a receptor‐independent manner. Using a Notch‐sensitive Recombination signal binding protein for immunoglobulin kappa J region (RBPJ) reporter assay, we found that basal levels of Notch signalling were significantly lower in prostate cancer cells compared to benign cells. Accordingly pharmacological Notch pathway blockade did not inhibit cancer cell growth or viability. In contrast to canonical Notch targets, HES6, a HES family member known to antagonize Notch signalling, was not regulated by Notch signalling, but relied instead on androgen levels, both in cultured cells and in human cancer tissues. When engineered into prostate cancer cells, reduced levels of HES6 resulted in reduced cancer cell invasion and clonogenic growth. By molecular profiling, we identified potential roles for HES6 in regulating hedgehog signalling, apoptosis and cell migration. Our results did not reveal any cell‐autonomous roles for canonical Notch signalling in prostate cancer. However, the results do implicate HES6 as a promoter of prostate cancer progression.